NEEDS ANALYSIS FOR DEVELOPMENT OF DIGITAL TEACHING MATERIALS WITH AUGMENTED REALITY FOR OPTICAL INSTRUMENTS MATERIALS - Saputri, Indah; Asrizal, Asrizal (Physics Learning and Education, 2023)
The use of instructional materials in education is highly crucial to achieve the success of a quality learning process. This study aims to analyze the need for the development of digital instructional materials using Augmented Reality (AR) for the topic of optical instruments. The study investigates five main aspects: physics learning issues, student learning results, student characteristics, learning objectives, and challenges related to the optical instruments topic. The research subjects include three physics teachers and eleventh-grade students from MAN 1 Kota Padang. Data collection techniques used in this study comprise interviews, questionnaires, documentation, and literature review. The collected data, analyzed with appropriate instruments, are subjected to descriptive statistical analysis techniques. Based on the data analysis, the following results are obtained: 1) students are no longer interested in using printed instructional materials, and the existing teaching materials do not align with the school's context, 2) student physics learning results are categorized as low, 3) internal factors such as interest, motivation, and learning styles among students are still underdeveloped, 4)the learning objectives designed by teachers inadequately consider appropriate learning behaviors for the competency levels of eleventh-grade students in fundamental knowledge and skills, 5) the average scores in the physics National Examination (UN) for the optical instruments topic have been consistently decreasing each year, falling below the standard passing grade, 6) in conclusion, it can be inferred that the development of digital instructional materials using AR for the optical instruments topic is highly necessary for both teachers and students.